The concept of skeletal safety jacket / Nurul Syafiqah Mahmud and Muhammad Redza Rosman - Mahmud, Nurul Syafiqah; Rosman, Muhammad Redza (2019)
The subject matter of innovation in safety wear for construction has been discussed over a considerable period. Current research and statistical data show that safety wear innovations in construction especially in Malaysia are lagging behind other areas in the aspects of productivity, efficiency, and health, for which lack of innovation is to be blamed. This paper intends to illustrate the present status of construction innovation on safety and health wearables and the present statistics on Musculoskeletal Disorder diseases based on a review of current literature and research. This paper also aims to raise awareness on the Musculoskeletal Disease (MSD) among manufacturing and construction workers in Malaysia and tackle the problems by doing immediate innovation to prevent cases of MSD from increasing year by year. This paper also aims to elaborate on the innovation concept of a skeletal safety jacket. A methodology has been developed to make sure that the objectives of this innovation are achieved. Literature review and desk studies have been done to collect the data.